Impact of machine learning techniques in Privacy compliance - Pramod Misra, Neha Tiwari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In today's era, "artificial intelligence" (AI) and "machine learning" (ML) are integral to our daily life and to find solutions to complicated problems under a variety of conditions, capabilities we previously believed to be exclusive to humans. To increase its usage, most of our tasks are depended on AI and ML and are solved by them. Personal information, financial information, health information, etc are also shared, stored and processed by AI. With the advent of this, privacy became a major issue, which is believed to be solved by AI aided by ML. Furthermore, the protection of data privacy and machine learning (ML) in the beginning stage as well as the previous resolutions are the main priority on the privacy issues during the machine learning methods. This study is intended to provide a deep understanding of the importance of privacy protection problems and the application of machine learning in this regard